DEVELOPMENT AND PERFORMANCE EVALUATION OF POLYMERIC MEMBRANE FOR CARBON DIOXIDE SEPARATION UNDER WET FEED CONDITIONS - DORAISELVAN, KIRENRAJ (IRC, 2017)
Removal of CO2from raw natural gas is one of the most significant industrial gas separation process as it causes corrosion in pipeline and reduces the calorific value of the product. Membrane separation technology is currently the trending method for the separation of natural gas due to environmental friendly and economically feasible. Polymeric membrane are selected as it is a good candidate for efficient CO2removal from natural gas due to their high separation efficiency. However, the presence of humidity in feed causes swelling in membrane. Swelling causes the molecular structure of molecule to contract and reduces the permeability and increases the selectivity of membrane. Polyetherimide (PEI) is the selected choice of glassy polymeric membrane due to high gas selectivity, excellent thermal and mechanical strength and reasonable gas separation performance. In this study, polydimethyl siloxane/polyetherimide (PDMS/PEI) composite membrane was developed by film casting the developed polyetherimide (PEI) membrane. The developed membranes were characterized using Fourier Transformed Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), Thermo Gravimetric Analysis (TGA) and contact angle. The performance of the developed membranes were tested using a gas permeation unit. The prepared membranes was tested on the pure carbon dioxide (CO2) and pure methane (CH4) for permeability and selectivity between 2-8 bar under dry and wet conditions. It was observed that CO2showed higher permeance under dry condition. However, the permeance of CO2 decreased in wet condition and affected the performance of the membrane. Selectivity of membrane under dry condition showed better performance than membrane under wet condition. Besides, PDMS/PEI showed better performance than pure PEI under wet condition as it demonstrated higher selectivity. Based on the swelling degree, PDMS/PEI composite membrane showed lower swelling degree concluding as a potential water resistant membrane for gas separation